Promoter motifs required for c-mpl gene expression induced by thrombopoietin in CMK cells - Sunohara, Masataka; Sato, Iwao; Morikawa, Shigeru (Cellular and Molecular Biology, 2017)
Thrombopoietin (TPO) and its receptor, c-Mpl, are the central regulators of megakaryocyte development and platelet production and are also crucial to regulate megakaryocytopoiesis. TPO remarkably elevated c-mpl promoter activity, while the protein kinase C (PKC) inhibitors, GF109203, H7 and Calphostin C, clearly reduced the steady level of its promoter activity. In the present study, motifs crucial for c-mpl promoter activity induced by TPO treatment has been analyzed using a human megakaryoblastic cell line, CMK. Destruction of the –107Sp1 and the –57Sp1 sites in the c-mpl promoter enhancer region resulted in decrease of the promoter activity by 53.1% and 64.4%, respectively, and destruction of –69Ets and –28Ets elements dramatically decreased the promoter activity by 96.4% and 87.8%, respectively, while mutation of –77GATA moderately reduced the activity by 31.4%. The result was in agreement with our previous report that showed the crucial motifs in the c-mpl promoter for the promoter activity induced by PMA-treatment. This indicates that TPO-induced activation of the c-mpl promoter activity is fully modulated by transcription through a PKC-dependent pathway and the two Sp1 and two Ets motifs are crucial for the activation of the c-mpl promoter activity rather than a GATA motif in the c-mpl promoter of CMK cells.